Necessity of Affordable Housing in Major Cities of Maharashtra pre and post Covid 19 Pandemic Scenario: Addressing housing shortages and pandemic challenges in Maharashtra (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The study focuses on the Covid 19 pandemic situation in India, the role of the constructionindustry in the past, present, and future, and the need for affordable housing in Major cities ofMaharashtra. The Current scenario of housing fabric, the use of innovative, alternative materials,planning and project management strategies to overcome the need for adequate housing will bediscussed. Primarily in the housing sector many shortfalls exist in developing countries, particularlyIndia, in terms of housing conditions in many of the country's cities. Many studies have shown thatusing alternative and innovative materials results in cost savings in terms of labour, time, and money.The primary goal of this paper is to study current housing typologies, shortfalls in housing, majorreasons for Spreading of Covid 19 Virus and role of an architect in affordable housing.